PERAN PELATIHAN DAN MOTIVASI GURU TERHADAP KINERJA GURU PADA MADRASAH ALIYAH NEGERI (MAN) SAMPANG - Fitra Mardiana; Chamariyah; Siti Nurul Hasanah (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2020)
The purpose of study are: 1) To determine the description of the training, motivation, and performance of teachers at Madrasah Aliyah Negeri Sampang; 2) Test and analyze whether training and motivation simultaneously have a significant effect on teacher performance at Madrasah Aliyah Negeri Sampang. 3) Test and analyze whether training and motivation partially have a significant effect on teacher performance at Madrasah Aliyah Negeri Sampang. The results showed that 1) Training is a planning program designed to improve performance and to bring about measurable changes. Motivation is a condition that encourages or causes a person to make a change that takes place consciously. Performance is a manifestation of work performed by a person or organization which is usually used as a basis for evaluating individuals or organizations. 2) Simultaneously, training and motivation were responded very well by respondents so that it had a significant effect on teacher performance at Madrasah Aliyah Negeri Sampang, it was proven to be true and the hypothesis was accepted. 3). Partially, the training and motivation responded very meaningfully / very well by the respondents so that they had a significant influence on the performance of teachers at Madrasah Aliyah Negeri Sampang, it was proven to be true and the hypothesis was accepted.